Atypical morphological changes in thrombotic microangiopathic anaemia (TMA) with Southeast Asian ovalocytosis (SAO) coinheritance - Seman, Zainina; Hashim, Hafizah; Mohd. Yusoff, Mohd. Fauzi (Universiti Putra Malaysia, 2024)
Thrombotic thrombocytopenic purpura (TTP) is a known life-threatening condition of thrombotic microangiopathic (TMA) syndrome. Schistocytes are the crucial morphological clue for the diagnosis, which is uncommon in the blood films of healthy people. The atypical presentation, signs, and symptoms that resemble other clinical conditions may mislead the diagnosis. We report a case of a pregnant lady with Southeast Asian ovalocytosis (SAO) who developed TTP without an obvious schistocyte on the peripheral blood film. We hypothesise an individual with underlying SAO will exhibit less evidence of schistocytes due to red cell membrane rigidity. A high index of suspicion is crucial for early diagnosis of TTP, and daily monitoring of peripheral blood films may improve the outcomes. This case report highlights the atypical TTP and emphasises the importance of considering TTP as a potential diagnosis even in the absence of schistocytes.